Coherent Lagrangian swirls among submesoscale motions - Beron-Vera, F. J. (Proc Natl Acad Sci U S A, 2019)
The emergence of coherent Lagrangian swirls (CLSs) among submesoscale motions in the ocean is illustrated. This is done by applying recent nonlinear dynamics tools for Lagrangian coherence detection on a surface flow realization produced by a data-assimilative submesoscale-permitting ocean general circulation model simulation of the Gulf of Mexico. Both mesoscale and submesoscale CLSs are extracted. These extractions prove the relevance of coherent Lagrangian eddies detected in satellite-altimetry–based geostrophic flow data for the arguably more realistic ageostrophic multiscale flow.